2017
DOI: 10.1063/1.4971785
|View full text |Cite
|
Sign up to set email alerts
|

Edge anisotropy and the geometric perspective on flow networks

Abstract: Spatial networks have recently attracted great interest in various fields of research. While the traditional network-theoretic viewpoint is commonly restricted to their topological characteristics (often disregarding the existing spatial constraints), this work takes a geometric perspective, which considers vertices and edges as objects in a metric space and quantifies the corresponding spatial distribution and alignment. For this purpose, we introduce the concept of edge anisotropy and define a class of measu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 61 publications
2
17
0
Order By: Relevance
“…One recent example of such a measure is the edge anisotropy, which takes the spatial directionality of edges adjacent to a given node into account. It has been shown that edge anisotropy supplements traditional topological measures like degree or betweenness by indicating the orientation of flows underlying networks constructed from spatio-temporal data [17].…”
Section: Introductionmentioning
confidence: 99%
“…One recent example of such a measure is the edge anisotropy, which takes the spatial directionality of edges adjacent to a given node into account. It has been shown that edge anisotropy supplements traditional topological measures like degree or betweenness by indicating the orientation of flows underlying networks constructed from spatio-temporal data [17].…”
Section: Introductionmentioning
confidence: 99%
“…The contact with network theory 24 is made when the matrix representing the transfer operator is interpreted as the adjacency matrix of a network [1][2][3][4]17,22,23 , so that the weight of a link between two nodes is given by the amount of flow between the corresponding spatial locations. An alternative viewpoint in characterizing fluid flows with network techniques assigns links between spatial regions according to statistical correlations between their dynamical variables, leading to correlation-based flow networks [25][26][27] and making a connection with the broad field of climate networks [28][29][30][31] .…”
Section: Introductionmentioning
confidence: 99%
“…Molkenthin et al 62 analyze networks constructed from correlations among variables undergoing advection-diffusion-reaction dynamics. The network perspective is used to demonstrate that the local anisotropy (a member of a new class of spatial network characteristics) of edges incident to a given vertex provides useful information about the local geometry of the flow represented by the network.…”
Section: Correlation-based Flow Networkmentioning
confidence: 99%